2010
DOI: 10.1371/journal.pone.0012039
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Sperm Motility Inhibiting Factor from Caprine Epididymal Plasma

Abstract: Several studies have been reported on the occurrence of sperm motility inhibiting factors in the male reproductive fluids of different mammalian species, but these proteins have not been adequately purified and characterized. A novel sperm motility inhibiting factor (MIF-II) has been purified from caprine epididymal plasma (EP) by Hydroxylapatite gel adsorption chromatography, DEAE-Cellulose ion-exchange chromatography and chromatofocusing. The MIF-II has been purified to apparent homogeneity and the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 34 publications
(53 reference statements)
3
30
4
Order By: Relevance
“…Hoskins and associates [18,32], in a novel in vitro model, triggered forward motility in the immature (immotile) sperm derived from bovine caput epididymis by incubation in presence of epididymal or seminal plasma and theophylline. Subsequently, from caprine epididymal plasma, pursuing to identify the extracellular proteins and their role in biochemical regulation of sperm motility, Jaiswal et al [33] and Das et al [34] have purified and characterized a motility initiating protein (MIP) and a motility inhibitory factor (MIF), respectively.…”
Section: Motility Initiating Protein and Motility Inhibitory Factormentioning
confidence: 99%
“…Hoskins and associates [18,32], in a novel in vitro model, triggered forward motility in the immature (immotile) sperm derived from bovine caput epididymis by incubation in presence of epididymal or seminal plasma and theophylline. Subsequently, from caprine epididymal plasma, pursuing to identify the extracellular proteins and their role in biochemical regulation of sperm motility, Jaiswal et al [33] and Das et al [34] have purified and characterized a motility initiating protein (MIP) and a motility inhibitory factor (MIF), respectively.…”
Section: Motility Initiating Protein and Motility Inhibitory Factormentioning
confidence: 99%
“…Immobilin was reported as high molecular weight protein and decrease sperm motility by increasing viscoelastic drag. But detailed mechanism of action of these proteins still remains unclear (Das et al, ; Dungdung & Majumder, ; Usselman & Cone, ). Hence, QF is different from other reported sperm motility inhibitory molecules from cauda region.…”
Section: Discussionmentioning
confidence: 99%
“…Esposito et al () showed that soluble adenylyl cyclase (sAC) deficient mice were not able to produce cAMP, thus infertile due to severe sperm‐motility defect. Das et al () reported MIF‐II reduced intracellular cAMP level of spermatozoa thus inhibited motility but detailed mechanism of action was not reported. However, in QF treated mature cauda spermatozoa no significant changes in intracellular cAMP concentration were observed (Figure d), which revealed the sperm motility inhibitory activity of QF was not mediated by modulating intracellular Ca ++ as well as cAMP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Equine semen is routinely submitted to centrifugation prior to cryopreservation to reduce the adverse effects of seminal plasma on post-thaw quality/motility (Moore et al, 2005). Likewise, the centrifugation of epididymal sperm can be also recommended for removal of epididymal fluid, once it suppresses the sperm movement (Usselman and Cone, 1983;Acott and Carr, 1984;Jeng et al, 1993;Das et al, 2010). The centrifuged samples, treated or nontreated, showed similarity in motion parameters (TM, VAP, ALH and RAP), confirming the hypothesis that epididymal sperm develops full motility when the epididymal fluid is removed and then exposed to the freezing extender.…”
Section: Discussionmentioning
confidence: 99%